PENGEMBANGAN MEDIA BERBASIS SOFTWARE ARCGIS UNTUK MENINGKATKAN MOTIVASI BELAJAR MAHASISWA PENDIDIKAN ILMU PENGETAHUAN SOSIAL PADA MATERI PETA UNIVERSITAS ISLAM NEGERI MAULANA MALIK IBRAHIM MALANG - Purwita, Ninja Panju; Muhayani, Ulfah; Nurfianto, Darma; Alfian, Achmad Hadi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2016)
Advancement in science and technology have enormous influence in the field of education. The media is one of tool that has an important role so that learning becomes more attractive, have variation and not boring. Making ArcGIS software-based media in learning how to create a digital map function shows the image and informations contained in the map so that students can understand well. The purpose of this study are:(1) Describe the procedures for developing ArcGIS software media learning IPS mapmaterial. (2) To determine the extent of ArcGIS software can improve the results of student motivation. The data in this development was obtained from the initial trials through expert validation results media and subject matter experts. Then, the data is retrieved from field trials in the form of a questionnaire to 10 students. After that, the data was obtained from the questionnaire results of the field test to the class C in academic year 2013 major in Social Education UIN Maulana Malik Ibrahim Malang. The results of questionnaire before media was revised in field trials at 76%. While the results of questionnaire after media was revised in field trials at 83%. The results of questionnaire before media was revised in field testing at 80%. While the media after result was revised in field tests at 96%. The second stage shows the percentage of 85% and 84%. While the second phase material comprehension test showed results of 81% and 76%.Keywords: ArcGIS software, digital map